2005
DOI: 10.1016/j.vaccine.2005.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of modified vaccinia virus Ankara based recombinant SARS vaccine in ferrets

Abstract: Severe acute respiratory syndrome (SARS) caused by a newly identified coronavirus (SARS-CoV) remains a threat to cause epidemics as evidenced by recent sporadic cases in China. In this communication, we evaluated the efficacy and safety of two SARS vaccine candidates based on the recombinant modified vaccinia Ankara (MVA) expressing SARS-CoV spike or nucleocapsid proteins in ferrets. No clinical signs were observed in all the ferrets challenged with SARS-CoV. On the other hand, vaccination did not prevent SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
200
1
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(213 citation statements)
references
References 15 publications
7
200
1
5
Order By: Relevance
“…Thus, the reduced production of both anti-inflammatory cytokines in the mOrVV-NHis-immunized mice after SARS-CoV infection may be related to the severity of the pulmonary inflammation in these mice. Weingartl et al (47) and Czub et al (48) reported that immunization with S protein expressing-recombinant modified VV Ankara (rMVA-S) induced stronger inflammatory responses and focal necrosis in liver tissues after SARSCoV challenge than in control animals. However, the precise mechanism underlying this liver inflammation has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reduced production of both anti-inflammatory cytokines in the mOrVV-NHis-immunized mice after SARS-CoV infection may be related to the severity of the pulmonary inflammation in these mice. Weingartl et al (47) and Czub et al (48) reported that immunization with S protein expressing-recombinant modified VV Ankara (rMVA-S) induced stronger inflammatory responses and focal necrosis in liver tissues after SARSCoV challenge than in control animals. However, the precise mechanism underlying this liver inflammation has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…However, recombinant vaccinia viruses expressing different foreign viral antigens, including the HA of influenza virus, have been shown to induce protective immunity in ferrets (Jakeman et al, 1989). A recombinant MVA expressing the spike or nucleocapsid protein of severe acute respiratory syndrome (SARS) coronavirus also proved to be immunogenic (Czub et al, 2005;Weingartl et al, 2004). It is therefore unlikely that the differences in protective effectiveness in monkeys and ferrets were related to the species that was used.…”
Section: Discussionmentioning
confidence: 99%
“…A recombinant vesicular stomatitis virus (VSV) expressing the SARS-CoV S protein was protective in mice (14) but has not been tested in primates, and the safety of VSV in humans remains to be established. Recombinant modified vaccinia Ankara (MVA) virus expressing SARS-CoV S protein was immunogenic and protective in rodent and primate models (15)(16)(17); however, one group found that the MVA/SARSCoV S-immunized ferrets developed hepatitis upon challenge with SARS-CoV (17). Vaccine constructs based on replication defective human adenovirus type 5 expressing a partial or full-length SARSCoV S protein have been evaluated for immunogenicity in rats and monkeys (18,19), but immunization depends on a high vaccine dose, and safety and protective efficacy remain to be demonstrated.…”
mentioning
confidence: 99%